Object tracking using firefly algorithm - Ming‐Liang Gao; Xiao‐Hai He; Dai‐Sheng Luo; Jun Jiang; Qi‐Zhi Teng (IET Computer Vision, 2013)
Firefly algorithm (FA) is a new meta‐heuristic optimisation algorithm that mimics the social behaviour of fireflies flying in the tropical and temperate summer sky. In this study, a novel application of FA is presented as it is applied to solve tracking problem. A general optimisation‐based tracking architecture is proposed and the parameters’ sensitivity and adjustment of the FA in tracking system are studied. Experimental results show that the FA‐based tracker can robustly track an arbitrary target in various challenging conditions. The authors compare the speed and accuracy of the FA with three typical tracking algorithms including the particle filter, meanshift and particle swarm optimisation. Comparative results show that the FA‐based tracker outperforms the other three trackers.